Sistem Informasi Berbasis Web Pada TK Islam Rabbani Jakarta Selatan - Pandhu Pramarta (Universitas Indraprasta PGRI Jakarta, 2020)
In this era, it is demanded to know and understand the development of the importance of technology. Technology provides convenience in helping human activities, especially in the academic world. At the moment Rabbani Islamic Kindergarten has not used the website as a tool for publication media and information exchange, so the information cannot be accessed by public in real time. In this research web is designed and created using SDLC (System Development Life Cycle) Waterfall Model. The research objective is designing and creating a website to facilitate easy access information, to cover wider area publication, and increase awareness. The results of this study are a website that helpful and easier for teachers, students and all stakeholders of the school to easily get information quickly and accurately. Referring to this, it is expected that by using a web-based information system, any information can be accessed and published to the people, making it easier for the public to get information at real time through an internet connection.